2008
DOI: 10.1007/bf03191019
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pregnancy on one-compartmental bio-metric blood loss calculations after cesarean section and gynaecological surgery

Abstract: To date there are no data in the literature on the procedure for the indirect measurement of blood loss during cesarean section, based on the post-operative drop in haemoglobin (Hb), which has been due to the lack of biometrically determined parameters for the calculation of blood volume in pregnant women. This study was therefore conducted to determine the applicability of the drop in Hb levels blood loss calculation during cesarean section, based on a model previously validated in non-pregnant women. We comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…0.184x, r = 0.599, SD = 0.059, p \ 0.0001). Popovic and Grujic (2008) found no significant difference between collected and calculated blood loss (using equation of Flordal) in 12 non-pregnant gynecological patients neither significant linear correlation (r = 0.155, p [ 0.5). In this case, small analyzed population (n = 12) could be reason for the absence of linear correlation between collected and calculated blood loss.…”
Section: Resultsmentioning
confidence: 49%
“…0.184x, r = 0.599, SD = 0.059, p \ 0.0001). Popovic and Grujic (2008) found no significant difference between collected and calculated blood loss (using equation of Flordal) in 12 non-pregnant gynecological patients neither significant linear correlation (r = 0.155, p [ 0.5). In this case, small analyzed population (n = 12) could be reason for the absence of linear correlation between collected and calculated blood loss.…”
Section: Resultsmentioning
confidence: 49%
“…Computer simulations have shown that physiological fluid volume received during operation could affect the blood loss calculations, but this occurred to be of minor importance (Bayer et al 2000;Lagneau et al 2005;Popovic and Grujic 2008). More important, as previously said, the patients received blood transfusion during operation and the received blood volume was considered when calculated blood loss was correlated with collected blood loss.…”
Section: Determination Of Blood Lossmentioning
confidence: 93%
“…The swabs may also have absorbed irrigation fluids, exudates or, in the case of cesarean section, and amniotic fluid (Popovic and Grujic 2008). Swabs can be washed to extract blood but this is a complicated procedure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemorrhage was defined as decrease in Hb/ Htc levels of 30% and 10% or greater, respectively, or calculated blood loss greater than 1500 ml, or any need of packed red cell transfusion [4]. Estimated blood loss was calculated according to a model which was found to be useful in indirect measurement of blood loss by Popovic et al in obstetric patient population [5]. Women with any risk factors associated with increased risk of postpartum hemorrhage, such as excessive uterine distension, antepartum hemorrhage, abnormal hemostasis profile, systemic diseases, anemia (Hb <8 g), pregnancy specific diseases, history of a prior postpartum hemorrhage, obesity (BMI >30) were all excluded from the study.…”
Section: Methodsmentioning
confidence: 99%